THE EFFECT OF NEW PENTAMETHINE CYA NINE DYES ON LEVEL OF hMSC NUCLEAR DNA DAMAGE IN VITRO - Kozyr Yu., Hubenia О. Aristova D. (My University, 2023)
We have studied the series of pentamethine cyanine dyes derived from benzothiazole heterocycles with different substituents emitted on near-infrared region. Incubation of human skin-derived mesenchymal stem cells with cyanine dyes 1871SI and 1749SI (1µM) leads to an increase in the induction of apoptosis in cells, increase in level of apoptosis-induced nuclear DNA fragmentation
ВПЛИВ НОВИХ ПЕНТАМЕТИНОВИХ ЦІАНІНОВИХ ФЛУОРЕСЦЕНТНИХ БАРВНИКІВ НА СТУПІНЬ УШКОДЖЕННЯ ЯДЕРНОЇ ДНК МЕЗЕНХІМАЛЬНИХ СТОВБУРОВИХ КЛІТИН ЛЮДИНИ IN VITRO